Buka Lanse Oral Poetry as a Cultural Communication Medium among the Jambi Malay Community in Sengeti Village - Lailatul Qhodri; Kurniati Ulfa (Journal of Communication, 2026)
This study aims to analyze the function of the Syair Buka Lanse as a medium of cultural communication for the Malay community of Jambi in Sengeti Village, Muaro Jambi Regency. This tradition is an integral part of traditional wedding ceremonies that convey moral, social, and religious messages through Malay-language poetry. The urgency of this study lies in the threat of extinction of oral traditions in the digital age as well as the lack of academic documentation on Syair Buka Lanse as a cultural communication system. This study employs Halliday’s theory of language functions, which encompasses expressive (personal) functions, regulative (social control) functions, and interactional (identity management) functions, as well as Liliweri’s intercultural communication approach, which emphasizes the reciprocal relationship between communication and cultural preservation. The approach used is qualitative descriptive, employing in-depth interviews, participant observation, and documentation of traditional leaders and practitioners. The research findings indicate that Syair Buka Lanse functions as a vehicle for cultural expression, social control, and the reinforcement of the identity of the Jambi Malay community. The expressive function is evident in prayers and advice that convey spiritual values and familial affection. The social control function is present through moral messages that teach etiquette, honor, and social responsibility. Meanwhile, the cultural identity function is manifested through the use of local language, symbols, and values that affirm the community’s identity.